Mitigating Interfacial Degradation in Sulfide-Based Solid-State Batteries using Polymer Coatings and Surface-Modified Solid Electrolytes - Shi, Bing-Xuan; Justus Liebig University Giessen (My University, 2025)
The growing market for electric vehicles is driving demand for high-energy-density batteries. Conven-tional liquid electrolyte batteries (LEBs) are nearing their energy-density limits, while solid electrolyte batteries (SEBs) using high-nickel cathode active materials (CAMs), solid electrolytes (SEs), and the lithium metal anode promise much higher energy densities. Sulfide-based SEs, such as Li6PS5Cl, exhibit particularly high ionic conductivity, making them promising candidates for industrial applications. How-ever, the interfacial degradation between sulfide-based SEs and electrodes limits their electrochemical performance. This dissertation explores innovative strategies to enhance the interfacial stability at both the cathode-electrolyte interphase (CEI) and the solid electrolyte interphase (SEI) in SEBs, focusing on polyelectrolyte coatings and modified sulfide-based SEs. Polyelectrolytes are selected as electrode coating materials in this dissertation for their flexibility, ease of processing, and lower cost than inorganic coatings. Moreover, they provide intrinsic ionic conductivity compared to neutral polymers, which is essential in SEBs but less of a concern in LEBs. While polymers as coatings in LEBs are well-studied, there is limited insight into their use in SEBs. This gap motivates this dissertation, demonstrating how polyelectrolytes enhance interfacial stability and performance in SEBs. The journey begins with exploring a polycation coating on LiNi0.83Co0.11Mn0.06O2 using the spray-drying method, revealing their potential and limitations. The polycation coating uniformly covers CAM particles to enhance cycling stability, but improved lithium-ion conductivity is needed to prevent capacity loss. Building on these findings, a subsequent study introduces a polyanion/amide polymer blend as a coating on LiNi0.9Co0.05Mn0.05O2, with the polyanion providing a lithium source to mitigate capacity loss and the amide polymer serving as a coating inducer. However, the polyanion/amide polymer coating demonstrates stiffness that needs more flexibility. As a result, a polyelectrolyte complex (PEC) coating is developed for LiNiO2 (LNO) cathode and a Si anode. This PEC employs a polycation to induce coating formation alongside a polyanion with a flowing nature that enhances both lithium-ion conductivity and flexibility. On the other hand, compared with the use of polyelectrolyte coatings, the modification of sulfide-based SEs via solvent treatment provides another approach to reducing the interfacial degradation of SEBs. This method improves the interfacial stability between the LNO cathode and the sulfide-based SE while preventing dendrite formation from the lithium metal anode. Additionally, modified sulfide-based SEs reveal a mechanism for enhancing cathodic performance different from the polyelectrolyte coating layer. This suggests that the combination of polyelectrolyte coatings with modifications to sulfide-based SEs could further bolster interfacial stability. This dissertation comprises four studies, including polyelectrolyte-coated electrodes and modified sul-fide-based SEs in SEBs. Each study employs a distinct approach to mitigate interfacial degradation and shows promising potential for industrial application. Collectively, these investigations provide a compre-hensive understanding of the strategies to improve interfacial stability while providing future strategies that can be further developed and studied.
Keywords: ddc:540